Driving innovation capability of wall decor craftsmen in Tegalalang Village, Gianyar, Bali - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti; I Made Hedy Wartana; I Ketut Yudana Adi (Universitas Muhammadiyah Malang, 2025)
Tegalalang Village in Gianyar, Bali, is recognized for its intricate wall décor craftsmanship, which significantly contributes to the local economy. However, craftsmen encounter challenges in innovation capability, market expansion, and business sustainability. This study aimed to enhance their innovation capacity through skill development, business strategy training, and digital adaptation to strengthen competitiveness and ensure industry sustainability. A participatory action research approach was implemented, involving 12 craftsmen in structured workshops and hands-on mentoring. The methodology encompassed a pre-test assessment of innovation capability, capacity-building interventions focused on product development, production efficiency, and digital marketing, followed by a post-test evaluation. The innovation capability instrument framework guided the assessment, addressing key aspects of manufacturing, sustainability, and business management. Findings demonstrated substantial improvements across all ten dimensions of innovation capability. Post-test results indicated enhanced knowledge in optimizing production processes, adopting digital marketing, and utilizing sustainable materials. The mean innovation capability score increased, affirming the program’s effectiveness. However, challenges persist in financial support, digital adoption, and global market expansion. This study underscores the value of structured innovation training in empowering SMEs in traditional industries. Future initiatives should emphasize long-term mentorship, financial access, and market expansion strategies to sustain innovation-driven growth.